2019
DOI: 10.1016/j.jofri.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Very affordable post mortem CT angiography kit: Feasibility study using immersion pump and 3D printed parts

Abstract: The high cost of commercial components and parts for post-mortem computed tomography angiography (PMCTA) has resulted in the development of a very low cost PMCTA-kit. It contains ubiquitous parts from hardware stores, and rapid prototyping derived models for 3D-printing. Design specifications have been tested and improved after finite-element modeling. A case study performed in using the final PMCTA kit parts for a PMCTA shows perfect vascular contrast without relevant leaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Further hardware employed: banana plugs, plastic bucket, silicone tubing. Including the mount/access parts [9], estimated total cost of all parts required for PMCTA (except fluid containers such as a bucket, single use floor covers, plastic covers, and contrast agent) remains under 200 CHF / EUR. Flow rate / voltage correlation was determined for both water and PEG-contrast agent solution (details see [8]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further hardware employed: banana plugs, plastic bucket, silicone tubing. Including the mount/access parts [9], estimated total cost of all parts required for PMCTA (except fluid containers such as a bucket, single use floor covers, plastic covers, and contrast agent) remains under 200 CHF / EUR. Flow rate / voltage correlation was determined for both water and PEG-contrast agent solution (details see [8]).…”
Section: Methodsmentioning
confidence: 99%
“…It is recommended that the submersible pump always be handled with two hands [8]. Bimanual handling is not always a given, and to improve submersible pump handling, we developed a series of 3D-designed and printed freely available support materials, including insertion catheters and vascular tourniquet sets, to facilitate handling of these small submersible pumps [9].…”
Section: Fig 3 Vascular Filling Of Thorax and Abdomenmentioning
confidence: 99%
See 1 more Smart Citation
“…As new applications arise, such as post-mortem computed tomography angiography (PMCTA), we found that some required parts may not be commercially available, whereas others may be built with convenience, so we developed and built them in-house [37]. For these parts, up to around ten iterations were used to reach the current designs.…”
Section: Tools and Tool Partsmentioning
confidence: 99%